Antibodies to Streptococcus pneumoniae Capsular Polysaccharide Enhance Pneumococcal Quorum Sensing - Masahide Yano (American Society for Microbiology, 2011)
ABSTRACT The use of pneumococcal capsular polysaccharide (PPS)-based vaccines has resulted in a substantial reduction in invasive pneumococcal disease. However, much remains to be learned about vaccine-mediated immunity, as seven-valent PPS-protein conjugate vaccine use in children has been associated with nonvaccine serotype replacement and 23-valent vaccine use in adults has not prevented pneumococcal pneumonia. In this report, we demonstrate that certain PPS-specific monoclonal antibodies (MAbs) enhance the transformation frequency of two different Streptococcus pneumoniae serotypes. This phenomenon was mediated by PPS-specific MAbs that agglutinate but do not promote opsonic effector cell killing of the homologous serotype in vitro. Compared to the autoinducer, competence-stimulating peptide (CSP) alone, transcriptional profiling of pneumococcal gene expression after incubation with CSP and one such MAb to the PPS of serotype 3 revealed changes in the expression of competence (com)-related and bacteriocin-like peptide (blp) genes involved in pneumococcal quorum sensing. This MAb was also found to induce a nearly 2-fold increase in CSP2-mediated bacterial killing or fratricide. These observations reveal a novel, direct effect of PPS-binding MAbs on pneumococcal biology that has important implications for antibody immunity to pneumococcus in the pneumococcal vaccine era. Taken together, our data suggest heretofore unsuspected mechanisms by which PPS-specific antibodies could affect genetic exchange and bacterial viability in the absence of host cells. IMPORTANCE Current thought holds that pneumococcal capsular polysaccharide (PPS)-binding antibodies protect against pneumococcus by inducing effector cell opsonic killing of the homologous serotype. While such antibodies are an important part of how pneumococcal vaccines protect against pneumococcal disease, PPS-specific antibodies that do not exhibit this activity but are highly protective against pneumococcus in mice have been identified. This article examines the effect of nonopsonic PPS-specific monoclonal antibodies (MAbs) on the biology of Streptococcus pneumoniae. The results showed that in the presence of a competence-stimulating peptide (CSP), such MAbs increase the frequency of pneumococcal transformation. Further studies with one such MAb showed that it altered the expression of genes involved in quorum sensing and increased competence-induced killing or fratricide. These findings reveal a novel, previously unsuspected mechanism by which certain PPS-specific antibodies exert a direct effect on pneumococcal biology that has broad implications for bacterial clearance, genetic exchange, and antibody immunity to pneumococcus.